Lack of influence of GTP cyclohydrolase gene (GCH1) variations on pain sensitivity in humans - Dionne Raymond A; Kim Hyungsuk (SAGE Publishing, 2007)
Abstract Objectives To assess the effect of variations in GTP cyclohydrolase gene (GCH1) on pain sensitivity in humans. Methods Thermal and cold pain sensitivity were evaluated in a cohort of 735 healthy volunteers. Among this cohort, the clinical pain responses of 221 subjects after the surgical removal of impacted third molars were evaluated. Genotyping was done for 38 single nucleotide polymorphisms (SNPs) whose heterozygosity > 0.2 in GCH1. Influence of the genetic variations including SNPs and haplotypes on pain sensitivity were analyzed. Results Minor allele frequencies and linkage disequilibrium show significant differences in European Americans, African Americans, Hispanic Americans and Asian Americans. Association analyses in European Americans do not replicate the previously reported important influence of GCH1 variations on pain sensitivity. Conclusion Considering population stratification, previously reported associations between GCH1 genetic variations and pain sensitivity appear weak or negligible in this well characterized model of pain.